2006
DOI: 10.1590/s0100-06832006000500016
|View full text |Cite
|
Sign up to set email alerts
|

Dinâmica do nitrogênio no solo e produção de fitomassa por plantas de cobertura no outono/inverno com o uso de dejetos de suínos

Abstract: RESUMO O uso de dejetos de suínos que antecede a instalação das plantas de cobertura de solo no outono/inverno é uma prática cada vez mais freqüente na região Sul do

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 12 publications
0
15
0
3
Order By: Relevance
“…Most of the N available to crops comes from the interaction between nitrogen fertilization and N mineralization/immobilization from crop residues and N from soil's organic matter (Silva et al, 2008). Low levels of nitrogen are justified in part due to babycorn crops have been done in succession to black oats, resulting in lower yields of dry matter and lower nitrogen absorption (Aita et al, 2006a), and also due to crop residues with high C:N ratio making micro-organisms that work in the organic material decomposition multiply rapidly, assimilating carbon and producing CO 2 and parallel to the carbon decomposition need to assimilate N (Aita et al, 2006b).…”
Section: Foliar Concentrations Of Macro and Micronutrientsmentioning
confidence: 99%
“…Most of the N available to crops comes from the interaction between nitrogen fertilization and N mineralization/immobilization from crop residues and N from soil's organic matter (Silva et al, 2008). Low levels of nitrogen are justified in part due to babycorn crops have been done in succession to black oats, resulting in lower yields of dry matter and lower nitrogen absorption (Aita et al, 2006a), and also due to crop residues with high C:N ratio making micro-organisms that work in the organic material decomposition multiply rapidly, assimilating carbon and producing CO 2 and parallel to the carbon decomposition need to assimilate N (Aita et al, 2006b).…”
Section: Foliar Concentrations Of Macro and Micronutrientsmentioning
confidence: 99%
“…Pig slurry (PS) is an organic alternative to chemical nitrogen (N) fertilizers that can increase production of winter and summer crops (Seidel et al, 2010;Moraes et al, 2014;Basso et al, 2016) and of cover crops (Aita et al, 2006). Many studies have found an increase in dry matter yield (DMY) of pastures in response to PS fertilization (Vielmo et al, 2011;Miranda et al, 2012;Zanine & Ferreira, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Assim, no planejamento das espécies a serem utilizadas no sistema de culturas, deve-se dar preferência a espécies leguminosas, quando se pretende implantar a cultura do milho no verão. Aita et al (2006) trabalharam com milho em sucessão a aveia solteira e em sucessão a aveia+ervilhaca. No cultivo de milho em sucessão a aveia+ervilhaca houve economia de 50% na quantidade de dejetos de suínos necessária para atingir a máxima produtividade de grãos do milho, indicando a interferência da leguminosa na produção de milho.…”
Section: Adubaçãounclassified
“…Pois, como a aplicação dos dejetos foi realizada antes da semeadura da cultura, a rápida nitrificação do N amoniacal dos dejetos poderá resultar em teores elevados de N-NO 3 -no solo, em um momento em que a demanda de N das plantas de milho ainda é pequena (Aita et al, 2006). Assim, a elevada precipitação pluviométrica ocorrida (Figura 1) resultou em perdas de N por lixiviação de N-NO 3 -e desnitrificação, uma vez que, em condições anaeróbias, o N-NO 3 -atua como aceptor de elétrons da cadeia respiratória de algumas bactérias, sendo reduzido à forma gasosa de N 2 (Dendooven et al, 1998).…”
Section: Adubaçãounclassified
See 1 more Smart Citation